The role of intraoperative superior hypogastric plexus blocks in pain management for total abdominal hysterectomy: a comparative study - Gundogdu, Elif; Gül Yılmaz, Tuğba (The European Research Journal, 2023)
Objectives: This study aimed to investigate the efficacy of intraoperative Superior Hypogastric Plexus Blocks (SHPBs) in managing postoperative pain following total abdominal hysterectomy, comparing pain scores and analgesic requirements between patients who received SHPBs and those who did not. Methods: A prospective, randomized, controlled trial was conducted on 70 female patients undergoing elective total abdominal hysterectomy. Patients were randomly assigned to either the SHPB group or the non-SHPB group. In the SHPB group, intraoperative SHPBs were administered after uterine removal. Postoperative pain scores were assessed using the Visual Analogue Scale (VAS) at various time points. Analgesic consumption and adverse effects were also recorded. Results: Patients in the SHPB group consistently exhibited lower pain scores compared to the non-SHPB group at various postoperative time intervals (p < 0.05). Initial analgesic requirements were significantly higher in the non-SHPB group, as was total analgesic consumption during the hospital stay (p < 0.05). No significant complications related to SHPB administration were observed. Conclusions: Intraoperative Superior Hypogastric Plexus Blocks demonstrated a potential benefit in reducing postoperative pain scores and analgesic consumption in patients undergoing total abdominal hysterectomy. These findings highlight the potential of SHPBs as an effective approach to enhance pain management in this surgical population, warranting further investigation and refinement of administration protocols.